Working with AI : Real Stories of Human-Machine Collaboration - Davenport, Thomas H; Miller, Steven M. (Cambridge, Massachusetts ; London, Massachusetts : The MIT Press, 2022)
An exploration of the future of work featuring real-world profiles of changing jobs and work arrangements in light of human/AI interaction
An exploration of the future of work featuring real-world profiles of changing jobs and work arrangements in light of human/AI interaction
Keywords: Artificial intelligence--Economic aspects; Artificial intelligence--Industrial applications; Information technology--Management.